(untitled) - DIANA LUTVITASARI, NUNGKY (Language Horizon: Journal of Language Studies, 2013)
Abstract UPT Aneka Industri dan Kerajinan Surabaya is the Technical Services Unit are carrying out Development and Small and Medium Industries Development and Human Resources through Technical Training in the field of Management, Technology, Production Process, Standards, Environment and Information. In improving the performance of the employees in that agency with the necessary changes in work procedures to improve leadership. There are so many ways to improve performance by way of leadership, from the nature of good leadership through effective leadership style so that employees can change their way of working. Because this company is a government company is bona fide and generates revenue from all areas of the required procedures for working very well ordered. Improve the ability and quality of work that the company will then be developed. Manage, serve and process are all ways good leadership to improve employee performance. Keyword:Employee,Leader, Introduction Nowadays, many people decide to become a leader. They do competition to find new innovation for their leadership and they want to be different with other leadership that had already started first. In the work of world every leader must be ready to get complain from their employees. Leadership itself is a person who has the skills or strengths, in particular skill or ability in a field that he is able to influence other to jointly undertake specific activities for the achievement of one or more goalsIntensive competition requires that manufacturers to be competitive with other manufacturers worldwide. Each company must be able to be effectively and efficiently to build an effective performance in order to achieve goals and success, then various components contained in a company should be run according with the objectives to be achieved. One component that has role very important is human resources, which is the leader/supervisor and employee/subordinates. Leadership is an organization or business. The leader of the organization must be able to use its authority in changing the attitudes and behavior of employees that want to work hard and wish to achieve optimal results. Leadership style leaders used can effect thoughts, feeling, attitudes and behavior members of the organization/subordinate (Nawawi, 2003). The sense of satisfaction in the work then the individual will display good personal organization, positive performance satisfactory companies and raised a willingness to undertake the level of labor productivity high for the organization and for improving achievement goals. The few things that can be identified from the dissatisfaction is absenteeism at work, lazy, malingering, absent from work, events strike, the use of time is not efficient and an even worse quit his job. Leadership can good or bad influence organizational climate, which in turn will direct impact on the effectiveness of the work of his subordinate. This leads to leaders must be able to create a conducive organizational climate that achieve job satisfaction, which in turn have an impact on the achievement of objectives organizational. Symptoms employee dissatisfaction can be seen from the absence of harmonious relation between the parties led to the employee, which is the leader less attention to the rights of the employees. For that leader has a very important role in improving job satisfaction employees. Based on the above, the study of the relationship style leadership and employee job satisfaction is very important to do. Definition of Leadership Leadership is one of the function of management human resources that make other people resolve work, maintaining morale and motivate subordinates (Dessler, 1997). From time to time the leadership of an attention to human, human being because of the leadership needed the limitation and advantages of certain human. On the one hand, man limited his ability to lead in other hand there are people who have excess capacity to lead. Here is the emergence of the need for leaders and leadership. Leadership the art of influencing other to directing the will, ability and effort in achieving goal leader. Leadership as an art show that activities affect others are individual, it is not the same way people or pattern between the leaders with one other. Therefore, an effective leader must be able to make purpose as the purpose of the organization, or otherwise make organizational goals into objectives and the ability of leaders lead it should result in all members of the organization felt that the purpose of the organization as a common goal. Mc Gregore in Agus Dharma (1992) says that scouting realize organizational goals and effectiveness when purpose of the organization is supported by all parties in the organization. Leadership is the power to move people and yourself toward a goal or vision particular, as well as power to transform the mobile community. Leadership the power to move people toward a goal or certain dreams. Obviously, there is someone who can move people toward a goal without it should be a true leader, but only a provocateur, even manipulator. Therefore, in addition to causing the motion, a leader is also a person who is able to produce a change or transformation in those he leads, he themselves and the system or community to which they belong. Thus, we recognize a true leader or not of the presence of motion and changes factors (A movement and Transformation Leader) as a prerequisite. Leadership is more detailed in Yulk (1998) is a process of influence, that influence the interpretation about events for followers, the choice of targets for group or organization, organization of work activities to achieves these objectives, the motivation of the followers to achieving goals, maintaining cooperation and team work, and obtaining the support and cooperation of the people who are outside the group or organization. According to Chandra (2005) a leader is a can create a situation in which his followers to step by step move towards their agreed upon with voluntary. Under this view, it is clear that a follow the leader because of his vision, mission formulation or target work. They believe in the leadership because what you want to accomplish along with his followers is a good a clear. They chose to follow because of the leaders are able to explore what has been unconsciously their dreams. This is a major factor determining success of a leader. According Arep and Cape (2002) leadership is properties that should be possessed by a leader, who in it is application to the person of consequences leaders are as follows: must take their own decision explicitly and precisely (decision making), must have the courage to accept this risk themselves, should dare to accept it is own responsibility (the principle of absolute of responsibility). Leadership Effectiveness Understanding of the effectiveness by John Ivancevich Nawawi (2003) is an assessment made in relation to achievement of individuals, groups and organization. The closer the achievement achieved with the expected performance, the more effective assessment of individuals, groups and organizations. By Drucker in Nawawi (2003), the effectiveness is to implement the right (doing the right), an achievement, effectiveness often described as “doing something right” means an activity or work that helps an organization reach the target. The effectiveness of leadership based on the theory of leadership situational (Contingency Theory). In practice, this view assume that no one leader is consistently using particular leadership style regardless of the situation it facts. This is, person’s leadership effectiveness depend on its ability to “read” the situation faces and adjust his style to the situation such a way that it effectively perform these function leadership (Siagian, 2003). The success of a leader is that if he can adjust your leadership style to the situation at hand. Situational leadership as well as taking into account factors conditions, time and space play role in a determining the choice of appropriate leadership style. So the effectiveness of leadership a person is determined by the ability to recognize to appropriate nature of the conditions it faces, whether the condition contained in organization and conditions that are outside the organization but have an impact on the course of the organization (Siagian, 2003). In other words, situational leadership theory assumes no single behavioral or leadership style that can affect human behavior or members of the organization to act, to do or work in all situations. Effective leaders have the behavior or leadership style that is flexible able to diagnose situation and use behaviors or styles leadership according to the circumstances they face (Nawawi, 2003). Nature and Characteristics of Leadership According to A.Dale Timpe (1991) there are eight (8) properties improve their productivity:The ability to concentrate, The emphasis on the value of a simple, Always hang out with people, Avoid artificial professionalism, Managing change, Select the people, Avoid doing all by yourself, Dialing with failure. According to Kantz in Nawawi (2003) three characteristic effective leaders are: 1) Have the technical skills such as the ability to apply specialized knowledge in the form of skills in the art. 2) Having the human skills that include the ability work together, understand and be able to motivate others, both of individual or groups. 3) Conceptual skills such as the ability of mental or intellectual to analyze and diagnose complex situation, in particular the time to take a decision. Similarly, according to Browers and Seashore (2003) suggest three characteristic of effective leaders, consisting of: a) Support the behavior of leaders who demonstrate to ability to enhance self-esteem and feeling that are considered important by others especially that people they lead. b) Ease of interaction of leader behaviors that stimulate, member organizations to develop relationship intimate and mutually satisfying. c) Ease of work that is a leader in helping behavior members carry out the work achieve the goals, through activity of job scheduling, coordination, planning, provision of resources such as equipment, labor, material or ingredients work and technical knowledge in the work. Terms and Character of the Leader According Arep and Cape (2002), an outline of a leader should ideally have three general categories, namely: 1) The ability to analyze and draw appropriate conclusions. He must be able to analyze something of a problem, situation or particular set of circumstances and draw conclusions appropriate. 2) The ability to develop an organization and can selecting, and placing the right people to fill position in the organization. 3) The ability to create such a way that the organization concerned running smoothly towards goals, ideals and the decision of higher level to the subordinates, that the goals and the decisions that are acceptable properly. Leadership Strategy Efforts to streamline the organization’s leadership must performed by using a strategy that guarantees the highest ability to achieve organizational goals. Strategy such leadership requires the ability to implement leadership functions effectively and efficiently in order to get support, without losing the respect, awe and obedience of all the members of the organization. The main strategy will only be realized if leaders in the running of social interaction with members of the group, showing the ability to understand, concerned and involved in the issues, and organization and its members. Leadership functions according to Nawawi (2003) are: Decision making function, functions of instruction, consultative function, delegates participatory function. a) Decision function Organization will only move dynamically if the leader have the power or ability to perform authority as decision-makers who will or should carried out by members of the organization. For that decision require courage because any definite decision at risk, especially if the process or mechanism is not meet the demands of the decision-making strategy implementation leadership, to be more accurate in leadership for streamline the organization, a leader must include members of the organization, according to the position and responsibilities. Inclusion can be done by provides an opportunity to provide input, such as creativity, initiatives, suggestion, opinions and feedback. Function instruction is order from a leader to realize the organization effect must be clear, both on the content terms and language that should be adjusted to the level skills or education of members who receive orders. Effective leaders don’t need to be emotionally error in executing command members. Leaders must be willing to look for the causes of errors, both in execution of the order on him as well as possible caused by a lack of clear leadership in providing orders. In giving the order should be followed as well to give an explanation to members of the organization will carry on the impact or consequences that would occurs when in command is done in correctly. Thus, it can be expected to be more careful execution of the command caution and careful, because a warrant maybe quite difficult for the implementing organization members. Consultative function is streamline the organization every leader must be prepared and willing to provide opportunity for member organization to consult in resolving the issues related to work and it is not impossible to consult on issues related to personal directly or indirectly to the job. Consultative function can also mean members of the organization were opportunity convey criticism, advice, information and opinions related to the job and the organization. This function is useful for improvement leadership, especially for new decision making, thus can improve leadership in effecting organization. Participatory function is the ability of leaders to include members of the organization according to position and authority in order to participate actively in relevant activities, can be realized through work in teams to reduce individual. Willingness shoot leaders and leaders below for participate in helping member organization carry work or resolve the problem faced by provide guidance, direction, discuss, resolve urgent work together. Delegatife function is every leaders need and has power or authority and responsibility should be implemented properly, appropriately and correctly, the leader must be able to divide the work and delegation of authority, and responsibilities in timely execution of the work and fair, as well as in decision making in accordance limit the power and responsibility that has been delegated. Control in Leadership Control in leadership do to keep that effect in the activities of members of the organization has always focused on mutually agreed goals. Control also significantly members of the organization to prevent and avoid activities that deviate from the goals of the organization. If to achieve a purpose, leaders have set up a way, but in implementation found a new, more effective and possible goals can be achieved more quickly, as well as risks low, then the leader must make decisions specify the use of the new method. Control activities in leadership must start the clarity of the objectives to be achieved by the organization, either leader and members of the organization. Organizational goals perceived as a common goal can be used intensively activities affect thought, feeling, attitudes and behaviors, through the direction of the members of the organization. Activity organizing the control is carried out by dividing duty or authority and responsibility into practice. The division of task is followed by its implementation by every member of organizations that have been implemented should be decided continue to perform the role of the controlled trough coordination, monitoring and redirection. So leader effective for activities that have been implemented should be decided continue to perform the role of the controllers so that the activities do not deviated from it is original purpose. Research Methodology Data can be a company's working hours for employees. This data then needs to be processed and converted into information. If the hours worked per employee is then multiplied by the value per-hour, it will produce a certain value. If the picture of each employee's earnings and then added together, will result in recapitulation salary to be paid by the company. Payroll is the information for the owner of the company. Information is the result of a process of existing data, or data that can be interpreted as having meaning. Information will unlock everything that is unknown. Basically, this research is categorized as qualitative research, since the data are in the form of words or sentences which are separated according to each category in order to get the conclusion (Arikunto, 1996:243). In this study, entitled "Leadership in Improving Employees' Performance in UPT Aneka Industri dan Kerajinan Surabaya". Based on the question "How does the leader role in improving the employees' performance?" and "How the employees' performance can be improved through the leader role?" Qualitative data is data in the form of words or in the form of verbal statements, not the robin figures. The qualitative data obtained through a variety of data collection techniques such as interviews, document analysis, focus group discussions, or observations that have been set forth in the court record (transcript). Another form of qualitative data was obtained through shooting images or video footage. Qualitative data include: 1. Inductive, which is based on one or a number of specific data to derive a conclusion by way of generalization, or analogy or causal relationship 2. Deductive, which is a process of thinking which is based on an existing propositions to acquire new proposition as the conclusion to the syllogism, the argument consisting of three propositions (the major premise, minor premise and conclusion or conclusions) 3. Comparative namely by outlining the similarities and differences between the two data objects under study. Subjects in this study were all employees. Researchers from the source there are 43 employees working in various industries and Crafts UPT Aneka Industri dan Kerajinan Surabaya. On the subject of this study, researchers led to all employees in order to improve their performance with the leadership role that will be applied. Leadership effectiveness is influenced by many diverse and varied, several factors related to leadership effectiveness, among other: task structure, leadership awareness of employees, skills and leadership skills, leadership traits superior and subordinate relationships, management support and human resources, a position of power, subordinate effort, behavior management and external coordination, of those factors when analyzed can be made a set of factors is smaller than the initial factors, namely: leadership factors, factors boss and subordinates and environmental factors. Based on these factors can be seen how the relationship with the leadership of subordinates in decision making and problem solving. Leadership style reflect the relationship in this study is how the leader relates to subordinates in order to improve the performance of the good and positive in an institution. Effective leadership that is able to run by leaders. Will be able to streamline the organization and increase employee productivity. With the respect to this benchmark in studying leadership in effective institutions can be seen from: achieving the institution itself, employee satisfaction and development of the company itself. So, if the factors of leadership effectiveness can be carried out well and the leadership is able to apply his leadership style according to the situation and condition is going to reach benchmark of effective leadership, it has been demonstrate effective leadership and employee productivity indirectly itself will increase. Data and information collection is a process of obtaining data and preparing useful to describe that result of data collected to be use as information, for example as part of a process improvement or similar project. The purpose of data collection is to obtain information to keep on way, to make decisions about the important issues, and also to give information on the others in specific topic. In general the data collection is to answer the problems that will be discussed as well as provide information about the problem and issues. In this study the data of things that can be applied by employees is the attitude of leadership, responsibility and attitude performance. All that can be applied when the employee aware of the importance of improved performance in an institution. The effect of the attitude of a leader can also affect how the performance of its employees whether they are good or bad. Therefore, a good attitude and decisive leadership is needed in the soul of a leader so that the performance of employees and leaders to get maximum results. By applying the managerial role of the leader in the employee's performance is expected to improve the performance of employees in a company or institution. Employees can apply the leadership that has been adopted by leaders in the office working on a task or attitude in the office everyday. Given such, will appear sustainable attitude among employees and leaders that will create a good performance. The research instrument is any equipment that is used to acquire, manage, and interpretation information from the respondents who performed the same measurement pattern. Research instrument designed for one purpose and cannot be used in another study. Peculiarities of every object of research led to a researcher must design their own instrument used. Arrangement for each research instrument is not always the same as the other studies. This is because the purpose and mechanism of action in any research techniques also vary. Several types of instruments in the study were as follows: 1) Test The test is a series of questions or exercises or other tools used to measure the skills, measurement, intelligence, ability or talent possessed by individuals or groups. 2) Questionnaire or questionnaires Questionnaires are a number of written questions used to obtain information from respondents in terms of their personal statements, or the things that he knew. 3) Interview (interview) Interview is used by researchers to assess the state of a person, for example to find data on student background variables, the elderly, education, attention, attitude towards something. 4) Observation In the sense that observational studies are conducted direct observations, observations can be done with the test, questionnaire, range images, and sound recordings. Observation contains a list of the types of activities that may arise and will be observed. 5) Graduated scale (ratings) Rating or a graduated scale is a measure of the scale, subjective made. Although this produces a graduated scale data rude, but enough to give specific information about the program or person. This instrument can easily provide an overview of performance, especially in the performance of duty, which shows the frequency of appearance of the properties. In preparing the scale, which needs to be considered is how to define a variable scale. What is in question should be what can be observed respondent. 6) Documentation Documentation, from the origin of the document, which means that the written stuff. In exercising methods of documentation, research investigating the written objects such as books, magazines, documents, regulations, minutes of meetings, and so on. Register questionnaire is a series of questions posed to the respondents in order to collect information from respondents about the object being studied, either in the form of opinions, responses, or himself. As a research instrument, then these questions should not deviate from the direction that will be achieved by the proposed project, which is reflected in the formulation of hypotheses. Thus the list of questions that must be filed with the tactical and strategy so as to filter out the information required by the respondent. Questions raised by the respondent should be clear formula, so researchers will receive the right information from the respondents. Because the respondent and the interviewer can interpret the meaning of a sentence different from the intent of researchers, so that the contents of the question cannot be answered precisely. Besides, it should also be noted that where the direction is achieved, given no clear direction may not be able to formulate a list of questions adequately. Compile a draft list of questions is actually a collective work across research team members. Involvement of all members of the research team will contribute research instrument construction completion. Steps in compiling a list of questions are determination of the required information, determination of the data collection process, preparation of the research instrument, testing instrument research. Result and Discussion Basically a company or institution can run smoothly when it has a strong foundation. And foundation here in question is a leader. When a leader has a dominant role in the company or institution, then the employees will follow the rules and will get good results in the form of improved performance. Therefore, there is no doubt that the role of leadership can improve employee performance. The Leader Role in Improving Employees’ Performance The role of leadership is crucial in a job. Who first determined is to choose a leader who can truly lead a company or institution. When we get a leader who deserves to lead the leader must have a vision and mission for the welfare of its employees by way of improving the performance of employees. A leader does not have to give orders to his subordinates or employees to do something, but by way of an example, the employee will follow what their leaders are doing as long as it's true. The employees’ performance can be improved through leader role Leadership is one of the issues in the management which is still interesting enough to be discussed until today. Mass media, both electronic and print, often featuring opinion and conversation discuss about leadership. Leadership role and strategic importance to the achievement of the mission, vision and goals of an organization, is one of the motives that drive people to always investigate the intricacies associated with leadership. Quality of leadership is often regarded as the most important factor in the success or failure of the organization as well as the success or failure of a business-oriented organizations in both the public and, generally perceived as a success or a failure of leadership. Once the importance of the issue of the role of the leader so that the leader be the focus of interest to researchers in the field of organizational behavior. Organizations that succeed in achieving its objectives and be able to fulfill its social responsibility will depend on the leadership. When the leader is able to perform well, it is possible that the organization will achieve its goal. An organization needs an effective leader, who has the ability to influence the behavior of its members or subordinates. Leadership style is a way used by a leader in influencing the behavior of others. Leadership style is the norm of behavior that is used by a person when the person is trying to influence the behavior of others. Each style has advantages and disadvantages. A leader will use the appropriate leadership style and personality skills. Every leader in providing care to foster, promote and direct all potential employees in the environment have different patterns with each other. The difference is caused by different leadership styles also vary from each leader. Correspondence between leadership styles, norms and organizational culture is seen as a key prerequisite for the successful achievement of organizational goals. Leader etymologically derived from the word "pimpin" (lead) means guided or guided, so in which there are two parties that led (the people) and the lead (priest). Having added the prefix "pe" to "leader" (leader) means those who influence others through the process of communication so that the authority of the act is something other people achieve specific goals. Is a leader who has the ability to influence individuals and groups can work together to achieve the intended purpose. Hendry in Kartini Kartono Pratt Fairchild (2006:38-39) argues that leaders in the broad sense is a person who leads by way of initiating social behavior by regulating, indicating, organize or control efforts / attempts of others or through prestige, power or position. Anagora (1992) in Harbani (2008:5) argues, that leadership is the ability to influence others, through communication either directly or indirectly, with the intention to drive people to the understanding, awareness and happy to follow the will of the leadership of the leadership is defined as the process of influencing and directing a variety of tasks related to the activities of the group members. Leadership is also defined as the ability to affect a variety of strategies and objectives, the ability to influence the commitment and devotion to duty in order to achieve common goals and capabilities affect the group in order to identify, nurture and develop organizational culture (Stogdill in Stoner and Freeman 1989: 459-460). Elements of leadership according to Stogdill is he involvement of members of the organization as a follower, distribution of power among the leaders of member organizations, legitimacy granted to followers, leaders influence followers through a variety of ways. Leadership is an activity to influence the behavior of others so that they would be directed to achieve certain goals. Leadership is defined as the ability to move or motivate some people to simultaneously perform the same activities and focused on achieving the goal. From the above, it is basically a leader who has the ability to move others and be able to influence that person to do something in accordance with the goals to be achieved. Conclusion Leadership is one of the function of management human resources that make other people resolve work, maintaining morale and motivate subordinates (Dessler, 1997). From time to time the leadership of an attention to human, human being because of the leadership needed the limitation and advantages of certain human. On the one hand, man limited his ability to lead in other hand there are people who have excess capacity to lead. Here is the emergence of the need for leaders and leadership. The success of a leader is that if he can adjust your leadership style to the situation at hand. Situational leadership as well as taking into account factors conditions, time and space play role in a determining the choice of appropriate leadership style. So the effectiveness of leadership a person is determined by the ability to recognize to appropriate nature of the conditions it faces, whether the condition contained in organization and conditions that are outside the organization but have an impact on the course of the organization (Siagian, 2003). In other words, situational leadership theory assumes no single behavioral or leadership style that can affect human behavior or members of the organization to act, to do or work in all situations. Effective leaders have the behavior or leadership style that is flexible able to diagnose situation and use behaviors or styles leadership according to the circumstances they face (Nawawi, 2003). In this study the data as the information needed to give an overview of the research. Data is something that does not have any meaning for the recipient and is still in need of a treatment. In this case, the data can be regarded as an object and a subject of the information is useful for the recipient. Information can also be caled as a result of processing or data processing. Quality of leadership is often regarded as the most important factor in the success or failure of the organization as well as the success or failure of a business-oriented organizations in both the public and, generally perceived as a success or a failure of leadership. Once the importance of the issue of the role of the leader so that the leader be the focus of interest to researchers in the field of organizational behavior. Organizations that succeed in achieving its objectives and be able to fulfill its social responsibility will depend on the leadership. When the leader is able to perform well, it is possible that the organization will achieve its goal. An organization needs an effective leader, who has the ability to influence the behavior of its members or subordinates. Thus, a leader or head of an organization will be recognized as a leader if he can have an influence and capable of directing his subordinates towards the achievement of organizational goals. Suggestion Expectations of the employees are in the presence of a wise leader and able to adjust the structure of the company or institution can work to change the existing errors in the body corporate. In the end, that the existence of a leadership role within a company or institution can improve and enhance the performance of employees and can form a good partnership between employees and management. REFERENCE Peraturan Gubernur Jawa Timur, 2008, Organisasi dan Tata Kerja Unit Pelaksanaan Teknis Dinas Perindustrian dan Perdagangan Provinsi Jawa Timur, Surabaya. Prayoga, Sondra, 2011, The Role of Exhibition to Increase Foreign and Domestic Market Activity TIU (Technical Implementation Units) REPTC (Regional Export Training and Promotion Center) of East Java. http://id.wikipedia.org/wiki http://id.wikipedia.org/wiki/DEKRANASDA www.google.com www.blogspot.com